Mechanisms of career agency: A longitudinal perspective - Jonczyk Sédès, Claudia (My University, 2016)
Looking at career agency throughtout the career life-cycle in a professional service firm (LegalCo) we find distinctive practices of career agency that come with the tasks and roles of different career stages. Our findings illustrate how these differences in career agency are related to different dimensions of subjective career success. Tracking patterns of career agency across three career stages from junior associate to partner we identify three overreaching mechanisms of career agency - seeking out (specific organisational actors), creating imprinting ties and playing on similarities - that account for distinctively different career experiences. Our study demonstrates that career ageny is an important concept to explain how specific ties become imprinted and thereby provide benefits across several career stages. Career agency is also a key factor to explain how organisational actors may expoit (or not) homophily in their work context.
, 2016
Keywords: Career agency; Network dynamics; Imprinting